A PASE Approach towards (Adamantyl‐1)‐, Alkyl‐ and (Het)Aryl‐Substituted [1, 2, 4]triazolo[1, 5‐d][1, 2, 4]triazines: A Sequence of Two Solvent‐Free Reactions Bearing Lower E‐Factors. Issue 28 (26th July 2018) - Krinochkin, Alexey P.; Kopchuk, Dmitry S.; Giri, Kousik; Shtaitz, Yaroslav K.; Starnovskaya, Ekaterina S.; Khalymbadzha, Igor A.; Drokin, Roman A.; Ulomsky, Eugeny N.; Santra, Sougata; Zyryanov, Grigory V.; Rusinov, Vladimir L.; Chupakhin, Oleg N.
Abstract: A Pot, Atom, Step Economic (PASE) approach is reported towards [1, 2, 4]triazolo[1, 5‐d][1, 2, 4]triazines, substituted with the azole ring with pharmacophore residues, such as 1‐adamantyl or 2‐furanyl moieties, naproxen residues, as well aliphatic and (het)aromatic substituents, starting from easily available 1, 2, 4‐triazine‐5‐carbonitriles and carboxylic acids hydrazides. This approach involves a sequence of two solvent‐free reactions accompanied by the Dimroth rearrangement on the last step. The structures of the final Dimroth rearrangement products were confirmed based on the DFT studies as well as the single crystal X‐ray analysis for the admantane‐substituted product. In addition, this method possesses lower E‐factors. Abstract : New adamantane‐substituted as ‐triazine and their azoloannelated derivatives have been synthesized from 5‐cyano‐1, 2, 4‐triazines by the reaction with carboxylic acid hydrazides. The method involves the use of two successive solvent‐free reactions: ipso ‐substitution of the cyano group at C5‐position of the 1, 2, 4‐triazine moiety by carboxylic acid hydrazide residues and followed by cyclocondensation reaction in POCl3 under neat, accompanied by Dimroth rearrangement. DFT calculations were carried out to get a better understanding on the mechanistic pathway of the reaction.